2019
DOI: 10.1371/journal.pgen.1008263
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Bacillus subtilis YidC1 (SpoIIIJ) insertase alleviate stress associated with σM-dependent membrane protein overproduction

Abstract: In Bacillus subtilis, the extracytoplasmic function σ factor σM regulates cell wall synthesis and is critical for intrinsic resistance to cell wall targeting antibiotics. The anti-σ factors YhdL and YhdK form a complex that restricts the basal activity of σM, and the absence of YhdL leads to runaway expression of the σM regulon and cell death. Here, we report that this lethality can be suppressed by gain-of-function mutations in yidC1 (spoIIIJ), which encodes the major YidC membrane protein insertase in B. sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…Work in Bacillus subtilis has shown that the toxicity of unregulated SigM, an alternative sigma factor, is due specifically to membrane protein overproduction, which is alleviated by a gain-offunction mutation to the membrane insertase YidC1 (Zhao et al, 2019b). Since only ~80 of the ~200 AlgU-regulated predicted membrane proteins are regulated by AlgB, AlgR, and AmrZ (Huang et al, 2019, Jones et al, 2014, Leech et al, 2008, Schulz et al, 2015, it is possible that a gain-of-function YidC mutant may suppress mucA essentiality in P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Work in Bacillus subtilis has shown that the toxicity of unregulated SigM, an alternative sigma factor, is due specifically to membrane protein overproduction, which is alleviated by a gain-offunction mutation to the membrane insertase YidC1 (Zhao et al, 2019b). Since only ~80 of the ~200 AlgU-regulated predicted membrane proteins are regulated by AlgB, AlgR, and AmrZ (Huang et al, 2019, Jones et al, 2014, Leech et al, 2008, Schulz et al, 2015, it is possible that a gain-of-function YidC mutant may suppress mucA essentiality in P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Backcrossing of mutations, together with genetic complementation studies, generates assurance that the observed phenotype is correctly linked to a specific genetic change. In previous studies, we have used CRISPR-Cas genome editing with custom gRNAs and repair templates to reconstruct mutations (29)(30)(31)(32). For each application, this entailed the design and cloning of an appropriate gRNA, followed by the design and cloning of a repair template.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that confer a selectable phenotype are routinely introduced by transformation. However, moving mutations and genetic constructions that do not confer a selectable phenotype can be more laborious, often involving screening of colonies for co-transformation of the desired change together with a selectable marker (genetic congression; (28, 29)). Here, we demonstrate that CRISPR-Cas9 mediated genome cleavage can also provide a strong selection for the transfer of mutations or genetic constructions into a recipient strain, even when it does not confer an immediately selectable phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…When discovered in E. coli, YidC was demonstrated to be essential for viability (Samuelson et al, 2000). Later, discovery of two different paralogs in Gram-positive bacteria, including B. subtilis and S. mutans, showed that at least one YidC is required for growth and survival under various environmental conditions, although they are not equally effective (Errington et al, 1992;Tjalsma et al, 2003;Hasona et al, 2005;Saller et al, 2011;Palmer et al, 2012;Mishra et al, 2019;Zhao et al, 2019). Subsequent proteomic analysis of S. mutans membrane preparations from mutants lacking either yidC1 or yidC2, coupled with characterization of the YidC1 compared to YidC2 interactomes, further revealed paralogspecific activities as well as overlap in their functional capabilities (Mishra et al, 2019;Lara Vasquez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane proteomic analyses of ffh, yidC1, yidC2, and ffh/yidC1 strains suggested a high degree of functional redundancy between YidC1 and YidC2, with gain of function mutations within yidC1 in a yidC2 background also identified (Mishra et al, 2019). A gain of function mutation has also been identified in Bacillus subtilis YidC1 (SpoIIIJ) enabling it to survive lethality caused by high σ M levels that interfere with intrinsic resistance to cell wall targeting antibiotics (Zhao et al, 2019). Work to characterize S. mutans YidC1 and YidC2 (SmYidC1 and SmYidC2) interactomes via immunocapture and chemical crosslinking experiments revealed several differences between apparent YidC1 and YidC2 interaction partners, and suggested both overlapping and individual substrate preferences (Lara Vasquez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%